Smart Skin Envelope - ROMANO, ROSA (Firenze University Press, 2022)
The Smart Skin Envelope research analyses the recent revolution that has taken place in the sector of planning and production of smart skin components, made up of dynamic layers. The aim is to identify the technological, functional, qualitative and performance parameters that guide the decisions of the actors in the innovation process. It explores the factors that drive them to develop solutions and proposals designed to transform the envelope of the building from a static to a dynamic element, featuring interoperable components that can interact with the input from the outdoor and indoor environments, in relation to which the smart skin acts as a system of boundary and delimitation. The proposed research programme explores in particular the sector of Smart Envelopes, setting as its priority objective the identification and definition of the energy performance, both through analysis of the state of the art and through the development of a facade component that is dynamic in terms of the adaptive variability of its performance.